2020
DOI: 10.1038/s41598-020-67299-6
|View full text |Cite
|
Sign up to set email alerts
|

The association of inflammasome and TLR2 gene polymorphisms with susceptibility to tuberculosis in the Han Taiwanese population

Abstract: Pulmonary tuberculosis (TB) caused by Mycobacterium tuberculosis (Mtb) is a global public health concern. Although inflammasome and the toll-like receptor 2 (TLR2) genes play an important role in host defense against Mtb, the associations of polymorphisms in these genes with TB risk are incompletely understood. A total of 230 TB patients and 213 individuals without TB were enrolled in this study. A significant difference in the frequencies of different AIM2 rs2276405 genotypes between the non-TB and TB groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
(56 reference statements)
0
5
0
3
Order By: Relevance
“…AIM2 binds to HIV dsDNA and may trigger acute inflammation and pyroptosis ( Ekabe et al., 2021 ). Regarding the AIM2 rs2276405 polymorphism, to our knowledge, only one study showed a significant difference in the genotype frequencies of this Single Nucleotide Polymorphism (SNP) between individuals with and without TB in a Taiwanese population ( Liu et al., 2020 ). In our study, no association between AIM2 polymorphisms and the occurrence of TB or its clinical presentations or inflammasome-related cytokines was observed.…”
Section: Discussionmentioning
confidence: 95%
“…AIM2 binds to HIV dsDNA and may trigger acute inflammation and pyroptosis ( Ekabe et al., 2021 ). Regarding the AIM2 rs2276405 polymorphism, to our knowledge, only one study showed a significant difference in the genotype frequencies of this Single Nucleotide Polymorphism (SNP) between individuals with and without TB in a Taiwanese population ( Liu et al., 2020 ). In our study, no association between AIM2 polymorphisms and the occurrence of TB or its clinical presentations or inflammasome-related cytokines was observed.…”
Section: Discussionmentioning
confidence: 95%
“…Studies regarding human genetic variants of AIM2 are rare in infectious diseases ( 41 , 42 , 45 ). Recently, we investigated another SNV of AIM2 (rs35130877) in 288 patients with PTB and 288 HCs.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study of a Chinese Han cohort identified SNPs in PRRs, TLR8, and TLR9, which were found to be associated with the development of TB [ 178 ]. In another study with a Han Taiwanese population [ 179 ], the C-T haplotype in the TLR2 gene, in comparison with the most common T-T haplotype, was associated with an increased risk for TB. There is evidence to justify further evaluation of TLR2 polymorphisms and their effect on TLR2-dependent signaling as these findings can provide insight into the development of TB therapeutics [ 195 ].…”
Section: Host Genetic Factorsmentioning
confidence: 99%
“…Lastly, although not a receptor involved in the phagocytosis or uptake of M.tb , multiple recent studies have examined polymorphisms in the vitamin D receptor (VDR) in different populations for their association with increased susceptibility to TB infection [ 183 , 184 , 185 , 197 ]. Other important immune factors in which SNPs have been recently studied include NLRP3 [ 186 ], AIM2 [ 179 , 187 ], and C-type lectins [ 188 , 189 ].…”
Section: Host Genetic Factorsmentioning
confidence: 99%